Thomas Kyd's mystery play: myth and ritual in 'The Spanish tragedy' - Ardolino, Frank R. (American university studies / 4, 1985)
First full-length study in English of "The Spanish Tragedy". Original analysis of the mystery subtext: the play as a detective mystery, an allegory, and a mystery ritual with Hieronimo as hierophant carrying out revenge and destiny.